Queer(ing) Italian-Canadian Literature: The Case of Steve Galluccio - Canton, Licia (Italian Canadiana)

(untitled) (Iter Press, 2023)
Montreal playwright Steve Galluccio states, “Italian immigrants, they weren’t gay.” The traditional values of Italians in Canada have often led to the marginalization of members of the LGBTQ+ community. For some, being queer and being of Italian origin is irreconcilable. Traditionally, the queer experience is not acknowledged in Italian immigrant homes. Today, there is still some reticence in the Italian-Canadian community, in both private and public spaces. Galluccio writes about his Italian origins and about being openly gay. Through his writing, he brings together two communities (LGBTQ+ and Italian Canadians) that often seem disconnected. This paper discusses Galluccio’s contribution to Italian-Canadian literature. It introduces his works, from the very popular Mambo Italiano to the most recent At the Beginning of Time, and looks at the connection between his literary contribution, Italian heritage, and queer identity.